PENDEKATAN TEOLOGIS DALAM MEMAHAMI MAKSUD SYARIAT DAN HUKUM YANG TIDAK DISEPAKATI - Adinda Ayu Kisdiyanti; Ashif Az Zafi (FKDP (Forum Komunikasi Dosen Peneliti), 2020)
Fiqh proposal is a method in exploring and establishing Islamic law. The science of ushul fiqh is useful to guide the mujtahid in correct syariah law and the results can be accounted for. Through the of fiqh can also be found a way out in solving the arguments that seem to conflict with each other. Even though the arguments in the study of Usul fiqh such as qiyas, istihsan, mursalah problems, istishab, and urf can be used as a basis for establishing laws and issues not clearly explained directly by the text. The scholars agreed to declare God as the party who was authorized to make the law in Islamic law. In this context, God is an makes the Shari'a, determines, raises and as a source of law. On this basis there is no Shari'a in Islam unless it is sourced from God. Because, God created man on earth and God also sets the rules about human life. This phenomenon ultimately encourages writers to conduct scientific research on religion. The approach to religion will experience significant development. This is indicated by an approach to religion that not only focuses on theological aspects, but penetrates other disciplines of the humanities.